Studi Perubahan Pola Ruang Pesanggrahan Ambarrukmo Yogyakarta Tahun 2004 - 2021 - Tyas, Paula Nugraheni; Kohdrata, Naniek; Bawono, Rochtri Agung (Jurnal Arsitektur Lansekap, 2024)
Pesanggrahan Ambarrukmo is one of the historical legacies of the Keraton Yogyakarta which has a unique spatial pattern, historical and socio-cultural value. As a heritage building, it faces physical changes following the construction of the Ambarrukmo Plaza and the Royal Ambarrukmo Hotel’s renovation. This study aims to determine the changes in spatial patterns before and after the construction of Ambarrukmo Plaza and the renovation of the Royal Ambarrukmo Hotel (2004 - 2021). The research method in this study is qualitative with a cultural studies approach and the triangulation methods in the form of interviews, observations and documentation combined with literature study. Physical changes occurring in Pesanggrahan Ambarrukmo have reduced the semi-sacred and profane areas as well as profane areas’ open green spaces, while the sacred area is not affected. Plaza Ambarrukmo and Hotel Royal Ambarrukmo managed to be a buffer space for Pesanggrahan Ambarrukmo. The changes of Pesanggrahan Ambarrukmo as an effort to maintain its existence are the most appropriate way in this modern era. The role of the managements, government, and community are necessary to preserve Pesanggrahan Ambarrukmo.